Handbook of perinatal clinical psychology: from theory to practice - Beck, Cheryl Tatano; Wischmann, Tewes (Routledge, 2020)
Overview of Perinatal Maternal Stress / Dawn Kingston & Muhammad Kashif Mughal -- Fetal exposure to mother's distress : new frontiers in research and useful knowledges for daily clinical practice / Catherine Monk, Sophie Foss, Preeya Desai, Vivette Glover -- "A precipice time" - Reproductive Biotechnology - psychosocial impact and unintended consequences / Joan Raphael-Leff -- Psychological impact of infertility and assisted reproduction / Tewes Wischmann -- Prenatal diagnosis : psychological impact and parents' experience in presence of fetal anomalies / Joann Paley Galst -- Miscarriage and pregnancy loss / Natalene Séjourné, Nelly Goutaudier -- Traumatic Childbirth : The Ever Expanding Ripple Effects / Cheryl Tatano Beck -- Beyond the blues : stress, emotional experiences of women and modalities of intervention in the postpartum period / Rosa Maria Quatraro, Pietro Grussu -- Parental emotional experiences after newborn hospitalization / Lisa S. Segre, Sue L. Hall -- Emotional and practical needs in postpartum women : the role of family and friends support, and social networks / Wendy Davis, Kimberly McCue, Brenda Papierniak, Christena Raines, -- Lita Simanis -- Breastfeeding and weaning: Parental well-being and psychological distress / Jenny Perkel -- Depression, anxiety and psychological distress in perinatal period / Jeannette Milgram, Alan W. Gemmill -- Risk factors for depression and anxiety in perinatal period / Alessandra Biaggi & Carmine M. Pariante -- Screening and early detection of women at risk of perinatal psychopathology / Alessandra Bramante -- Postpartum psychosis, bipolar disorders and mother-baby unit / Florence Gressier, Ingrid Lacaze de Cordova, Elisabeth Glatigny, Nine M.-C. Glangeaud-Freudenthal, Anne-Laure Sutter-Dallay.
Originally published in Italian as Psicologia clinica perinatale. Trento, Italy : Edizioni centro studi Erickson, S.p.A., c2018
Includes bibliographical references and index